Sucessão na agricultura familiar: as perspectivas dos jovens filhos de agricultores de municípios da região de Palotina-Pr - Gris, Vanessa Gleica Cantú (2017)
Succession in family farming has been an evidenced subject in recent years. The concern with the family farms has been notable due to the rupture of the old naturalness that used to exist about the destination of the farm and the family members because of the refusal of young people to succeed their paternal profession, followed by the unbridled migratory phenomenon towards urban areas. From this problem, the proposal of this study was to evaluate perspectives of young people, children of farmers, about family farming succession in cities around the region of Palotina-PR. Therefore, the research consisted by two sample groups: Group 1 - young people, children of family farmers, with farms in Palotina, Maripá, Assis Chateubriand and Terra Roxa, participating in the “Programa de Formação de Liderança Jovem” (which is known as Modular), promoted by an agroindustrial cooperative of the Western region of Paraná and Group – 2 young people, children of family farmers, living in rural communities in Palotina. The selection of these two research groups aimed to compare the succession perspectives of young people who are participating in a training, whose objective is to approximate them to the farming activities and cooperative practices, with the perspectives of young people who are not directly involved in this environment. The research, characterized as descriptive and exploratory, had the data collection instrument called PERSUMI, which was applied to 32 young people from Group 1 and 48 young people from Group 2, from July to September 2017. The results of this research reaffirm the migratory tendency of young people, children of farmers towards urban areas and evidence changes in the rural areas regarding higher education of the children of farmers, better quality of life than the one provided by the city, dissociation of the countryside from a hackneyed image of the rural and more opportunities for investment with the evidence of rural entrepreneurship. However, some barriers have not been overcome yet, such as lack of planning about the destination of the farm and the late succession. Finally, it was found that both groups were not expressively different, considering young people profile, farm profile and future perspectives regarding succession, concluding that only a quarter of the young people intend to succeed the paternal profession.